Comprehensive investigation of physicochemical and electrochemical properties of sulfonated poly (ether ether ketone) membranes with different degrees of sulfonation for proton exchange membrane fuel cell applications. (15th April 2017) - Parnian, Mohammad Javad; Rowshanzamir, Soosan; Gashoul, Fatemeh
Abstract: The investigation of the effect of various degrees of sulfonation (DS) is important for the selection and modification of hydrocarbon type membranes towards ion exchange applications. In this work, twelve kinds of sulfonated poly (ether ether ketone) membranes with different DS were prepared and their physicochemical and electrochemical properties were studied. The sulfonated polymers were prepared by sulfonation of PEEK and characterized by H NMR, FTIR, and XRD. Then, the different SPEEK membranes were prepared by the solvent casting method, and their morphology and homogeneity were investigated by FESEM. The effect of DS on the thermal (TGA and DSC), mechanical and oxidative stabilities, water uptake behavior, and ionic exchange capacity of the membranes was determined. Also, the proton conductivity of the membranes at different temperatures and relative humidities were measured. The results indicated that the SPEEK samples showed progressive deterioration of thermal stability, an increase of glass transition temperature, a decrease of the elastic modulus, and a decrease of the chemical stability with increasing of the DS. The proton conductivity of SPEEK membranes increased with DS, and for each membrane increased with increasing temperature and humidity. The results showed that moderate DS membranes (DS ∼ 65%) had acceptable mechanical, thermal, electrochemical, and chemical stability. Highlights: Investigation of effect of different sulfonation reaction times on PEEK properties. Preparation of SPEEK membranes with different degrees of sulfonation. Investigation of thermal and mechanical properties of different SPEEK membranes. Study of effect of DS on electrochemical and chemical properties of the membranes. Proton conductivity measurements in different temperatures and relative humidities.